Compulsory Military Service and Future Earnings: Evidence from a Quasi-Experiment - Muhammad Asali (Institute for the Study of Labor (IZA), 2015)
Using Israeli census data, this study provides new evidence on the long-term effects of military service on the earnings of veterans. Among Druze men aged 25-34, we find an economically and statistically significant positive effect of 18% on their wages. The respective effect for the 35-44 age group is 23%. The positive effects are large and intensify with time. Skill-enhancement and usual human capital accumulation do not explain the positive effect of military service. Networking and widening the circle of contacts during service are suggested as the most likely explanations.
Keywords: J24; J31; J45; 330; military service; future earnings; social capital